EVALUASI PEMANFATAAN DATABASE EBSCO DAN PROQUEST DALAM PENYUSUNAN LAPORAN PENELITIAN DOSEN FAKULTAS EKONOMIKA DAN BISNIS UGM TAHUN 2013-2015 MENGGUNAKAN ANALISIS SITASI - Maryatun, Maryatun; Purwaningsih, Heni (Journal of Documentation and Information Science, 2018)
Evaluation of the use of journal databases containing the same subject area is indispensable for budget efficiency. The evaluation of database utilization is closely related to the availability of information resources as a citation in the preparation of scientific papers. This research is quantitative descriptive research. The research method used is the method of documentation with the object of research citation/bibliography of Lecturer Research report FEB UGM year 2013-2015. The results showed that core journals majoring in Accounting is the Journal of Accounting and Economics with the largest citation frequency of 91 times; Department of Management Academy of Management Journal with citation frequency 65 times; and American Economics Review with a frequency of citation 21 times is the core title of the Department of Economics. In general, the utilization of EBSCO database ?Business Source Complete? and ProQuest ?ABI/INFORM Complete? as the citation for preparing the research report of FEB UGM lecturer for the period of 2013-2016 has been well utilized. The percentage of e-journal availability in the Business Source Complete database and the ABI/INFORM Collection database cited in the preparation of research report of FEB UGM majoring in Accounting as much as 703 titles (62.8%), Management Department available 655 titles (64.2%) and majors Economics is available 231 titles (44.6%). The ?Business Source Complete? EBSCO database and ProQuest ?ABI/INFORM Collection? are database aggregators that collect multiple journals from several publishers. In addition, the EBSCO Database ?Business Source Complete? provides more economics and business journals than the ProQuest ?ABI/INFORM Collection? database. However, ProQuest database ?ABI/INFORM Collection? is widely used by Lecturer of Management Department in preparing a research report.